ANALYSIS OF SHARE PERFORMANCE USING THREE FACTORS MODEL FAMA AND FRENCH (TFMFF) IN ILQ-45 STOCK PERIOD 2017-2020 - Rendra Arief Hidayat; Bayu Rama Laksono; Arfiana Dewi; Rizky Aditya Nugraha (Jambura Economic Education Journal, 2023)
Research conducted by Fama and French in 1996 showed that there were factors other than the beta that were significantly able to predict stock returns. However, several subsequent studies showed inconsistent results. The discrepancy between the results of previous studies prompted this research to be carried out. In this study, the researchers selected the stocks used based on the criteria for company profits and return on equity (ROE) offered by Warren Buffett. This study uses Buffett's criteria in selecting stocks that are used to analize TFMFF in estimating the return of stocks grouped into the Fama French portfolio. The method used is quantitative. The secondary data used are quarterly close price data, mining company equity value, Bank Indonesia interest rate (risk-free rate), and number of outstanding shares (number of shares outstanding). The results show that the TFMFF is accurate in predicting stock returns.